Transcriptome Analysis Reveals that Exogenous Melatonin Confers Lilium Disease Resistance to Botrytis elliptica - Xie, Xuehua; Han, Yu; Yuan, Xi; Zhang, Man; Li, Ping; Ding, Aiqin; Wang, Jia; Cheng, Tangren; Zhang, Qixiang (Frontiers in Genetics, 2022)
Leaf blight, caused by Botrytis elliptica (Berk.) Cooke, is a devastating disease that limits the production of Lilium in China and in other countries worldwide. Numerous studies have indicated that plants have evolved sophisticated and effective signal transduction and defense-related pathways in response to pathogen invasion. Recently, particular attention has been given to the action(s) of melatonin in plants in response to biotic stress, and the role of melatonin in plant–pathogen interactions has also been discussed. In this study, RNA-seq was applied to analyze the transcriptomic changes in Lilium leaves that were pre-treated and post-treated with melatonin after B. elliptica infection for 0 h, 12 h, 24 h, 36 h, and 72 h and then compare those changes with those of the control. Treatment with exogenous melatonin and infection with B. elliptica caused differential expression of a large number of genes in Lilium leaves. KEGG pathway analysis showed that, after melatonin treatment, the defense-related DEGs were mainly enriched in plant–pathogen interactions, plant hormone signal transduction, MAPK signaling pathways, phenylpropanoid biosynthesis, and phenylalanine metabolism. RT–qPCR was used to verify the expression changes of 12 DEGs, the results of which were consistent with the RNA-seq analysis results. The expression of DEGs related to the MAPK pathway were significantly different between the MB group and the HB group, suggesting that, via the MAPK signaling cascade, melatonin may play a role in the disease resistance of Lilium to B. elliptica. This study provides a new perspective and information for molecular-based breeding of Lilium disease resistance.